When viral myocarditis meets thrombosis tendency: deep analysis of a complex case report - Ding, Qian; Zhang, Yun; Li, Dongbei; Liu, Wenhua; Feng, Jing; Li, Shuang; Chen, Wei; Guo, Mu (Frontiers in Cardiovascular Medicine, 2025)
This case report presents a 43-year-old male patient with severe symptoms who was admitted due to dyspnea following physical activity, cough accompanied by fever, lower limb edema, and hemoptysis. The patient had a 20-year history of hypertension. Examinations revealed bilateral lower pulmonary artery thrombosis, a left ventricular thrombus, pulmonary infarction, and reduced left ventricular systolic function, with a lowest left ventricular ejection fraction (LVEF) of 26.5%. Genetic testing indicated the presence of methylenetetrahydrofolate reductase (MTHFR) (C677T) CT type and plasminogen activator inhibitor-1 (PAI-1) (4G/5G) 4G/5G type, while pleural fluid sequencing confirmed Epstein–Barr virus (EBV)/cytomegalovirus (CMV) infection, leading to a diagnosis of viral myocarditis. Treatment included low molecular weight heparin for anticoagulation, glucocorticoids, and measures to improve cardiac function. During treatment, the patient developed a cerebral infarction. Anticoagulation was maintained post-evaluation due to the PAI-1 mutation and was later adjusted to rivaroxaban. Following treatment, inflammatory markers and coagulation function improved, cardiac function recovered (LVEF increased to 53%), and the thrombus resolved. The combination of EBV/CMV infection with MTHFR and PAI-1 mutations synergistically induced thrombosis through the “virus-inflammation-gene” pathway. This case underscores the importance of early pathogen and genetic screening, as well as personalized anticoagulation strategies, such as substituting warfarin with rivaroxaban. The potential synergistic effect of infection and hereditary thrombophilia in multi-organ embolism warrants careful consideration.